2019
DOI: 10.21203/rs.2.16563/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Cesarean Section Maternal Health Outcome and its Determinants in Tigray Regional State, North Ethiopia.

Abstract: Back ground Cesarean section rate is increasing worldwide. However, the World Health Organization has declared that there is insufficient information on maternal outcome following cesarean section for decision making.Objective The aim of this study was to assess post cesarean section maternal outcome and its associated factors availing evidence for practice and policy.Methods Institution based cross-sectional study was conducted among 357 mothers who underwent cesarean section in six selected public general ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
5
4
1
Order By: Relevance
“…In this study, the overall poor maternal outcome was 19.5% with 95% CI (15.67%-23.97%). This is consistent with the study done in Okhaldhunga, Nepal (17.1%) (22) and Tigray, Northern Ethiopia, (19.3%) (11). But high compared to other studies conducted in developing countries, Sokoto, North Western Nigeria, reported 13.3% (23) and Durame General Hospital, Southern Ethiopia, reported 6.7% (24).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the overall poor maternal outcome was 19.5% with 95% CI (15.67%-23.97%). This is consistent with the study done in Okhaldhunga, Nepal (17.1%) (22) and Tigray, Northern Ethiopia, (19.3%) (11). But high compared to other studies conducted in developing countries, Sokoto, North Western Nigeria, reported 13.3% (23) and Durame General Hospital, Southern Ethiopia, reported 6.7% (24).…”
Section: Discussionsupporting
confidence: 89%
“…Data was collected using standardized and pretested questionnaires by interviewing women and record review of mother's undergone interview by using checklist. The data collection tool was adapted from similar studies conducted previously (11,12,(17)(18)(19). The tool addresses women's socio-demographic factors, obstetrics and medical factors and surgical related factors.…”
Section: Data Collection Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…The major shortterm complications found were wound infection 7%, endometritis 3.6%, and bleedings requiring blood transfusion 2.8%. In contrast, hysterectomy 1.7%, uterine rupture 0.6% and maternal death 0.28% were the significant long-term and serious maternal complications found [13] .…”
Section: Introductionmentioning
confidence: 82%
“…Data was collected using the data abstraction tool, which was prepared after reviewing previous literature [13,[15][16][17] and customized based on the objectives of this study.…”
Section: Data Collection Tool and Analysismentioning
confidence: 99%